2011
DOI: 10.1371/journal.pone.0024581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Streptococcus pneumoniae Strain Background on Complement Resistance

Abstract: BackgroundImmunity to infections caused by Streptococcus pneumoniae is dependent on complement. There are wide variations in sensitivity to complement between S. pneumoniae strains that could affect their ability to cause invasive infections. Although capsular serotype is one important factor causing differences in complement resistance between strains, there is also considerable other genetic variation between S. pneumoniae strains that may affect complement-mediated immunity. We have therefore investigated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 47 publications
0
29
0
1
Order By: Relevance
“…The isogenic capsular transparent-phase variants of the S. pneumoniae strain TIGR4 used in this study have been described previously (2,4,23,24). The 33 clinical strains used represent common multilocus sequence type (MLST) clones for 8 serotypes, and all isolates were obtained from nasopharyngeal cultures of asymptomatic children or from invasive S. pneumoniae infections in adults and children and were described by Hyams et al (19) (kind gifts from Brian Spratt, Imperial College, and Birgitta Henriques-Normak, Karolinska). PspC mutants of capsule-switched variants of TIGR4 were created by transformation using conventional methods with a pspC deletion construct made by overlap extension PCR as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The isogenic capsular transparent-phase variants of the S. pneumoniae strain TIGR4 used in this study have been described previously (2,4,23,24). The 33 clinical strains used represent common multilocus sequence type (MLST) clones for 8 serotypes, and all isolates were obtained from nasopharyngeal cultures of asymptomatic children or from invasive S. pneumoniae infections in adults and children and were described by Hyams et al (19) (kind gifts from Brian Spratt, Imperial College, and Birgitta Henriques-Normak, Karolinska). PspC mutants of capsule-switched variants of TIGR4 were created by transformation using conventional methods with a pspC deletion construct made by overlap extension PCR as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
“…Capsule-specific antibody titers for clinically relevant serotypes were measured using standardized enzyme-linked immunosorbent assays (ELISAs) with preabsorption with C-polysaccharide and serotype 22F capsular polysaccharide as described (http://www .vaccine.uab.edu/ELISA%20Protocol.pdf). Total IgG binding to S. pneumoniae (representing both anticapsular and antiprotein antigen activity), C3b/iC3b deposition, iC3b, FH, and Bf binding to S. pneumoniae after incubation in 20% serum for 20 min at 37°C were measured using flow cytometry assays and R-phycoerythrin goat anti-human IgG (Jackson ImmunoResearch) or fluorescein isothiocyanate (FITC)-conjugated antihuman C3 or iC3b, anti-FH, or anti-Bf (ICN) as described previously (2,12,15,16,19). As complement factor binding to S. pneumoniae is often biphasic with strongly positive and weakly positive populations of bacteria, results are presented as a fluorescence index (FI; percentage of positive bacteria multiplied by the geometric mean fluorescence index (MFI) in arbitrary units) (2,12,15); this ensures both intensity (geometric mean MFI) of complement factor binding and the proportion of positive bacteria are included in the data analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While numerous virulence factors undoubtedly contribute to the pathogen's ability to resist complement deposition and phagocytosis [23][24][25], two recent studies have illustrated the central dominance of the capsule in this strategy [24,26]. Both of these studies showed the fundamental importance of capsule by leaving the genetic background the same and only changing the capsule type.…”
Section: S Pneumoniaementioning
confidence: 99%